Two new records of Ravenelia species on legumes in Thailand - Ayawong, C.; Unartngam, J.; Chung, W. H. (International Journal of Agricultural Technology, 2020)
Ravenelia species were found in legume plants (family Fabaceae) in Thailand. Ravenelia stevensii occurred on Pterolobium macropterumin Lampang and Khonkean provinces, and Ravenelia neocaledoniensis on Vachellia farnesiana in NakhonPathom province. They produced different sporulation stages and spore morphology on their hosts. Ravenelia stevensii produced spore stages including spermogonial, aecial, uredinial and telial stages in the same host (P. marcopterum). Ravenelia stevensii have prominently appendages on teliospore surface and its structure size was very closely to voucher specimens. The rust fungus, R. neocaledoniensis was found only uredinial stage on V. farnesiana. The species were identified confirmation bymorphology and phylogenetic analysis using 28S rDNA. The results showed that R. neocaledoniensis was grouped together with the sequence obtained from GenBank database. The four squences of R. stevensii were clustered and separated from others Ravenelia species with 100% bootstrap value supporting. These rustfungi and host taxa were reported as a new record not only in Thailand but also in Southeast Asia.